2021
DOI: 10.1002/hep.31648
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Circles for Liver Allocation

Abstract: BaCKgRoUND aND aIMS: In February 2020, the Organ Procurement and Transplantation Network replaced donor service area-based allocation of livers with acuity circles, a system based on three homogeneous circles around each donor hospital. This system has been criticized for neglecting to consider varying population density and proximity to coast and national borders. appRoaCH aND ReSUltS: Using Scientific Registry of Transplant Recipients data from July 2013 to June 2017, we designed heterogeneous circles to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…By contrast, an optimization perspective10–12 could mean applying computational tools to design continuous allocation scores that maximize transplantation benefits while enforcing constraints, say, that logistical complexity does not increase too much and that organs are distributed equitably. Furthermore, because increased burden varies greatly by geography, an optimization approach could be used to design a geographically heterogeneous continuous allocation score 13,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, an optimization perspective10–12 could mean applying computational tools to design continuous allocation scores that maximize transplantation benefits while enforcing constraints, say, that logistical complexity does not increase too much and that organs are distributed equitably. Furthermore, because increased burden varies greatly by geography, an optimization approach could be used to design a geographically heterogeneous continuous allocation score 13,14…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because increased burden varies greatly by geography, an optimization approach could be used to design a geographically heterogeneous continuous allocation score. [13,14] Circle-based liver allocation is associated with a national increase of 2.0 h in mean distribution time. This delay in allocation is likely a delay in organ placement due to the increased number of centers required to place an organ.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, optimization methods were used to redesign district boundaries [10][11][12] for liver distribution and design geographically heterogeneous circular distribution. 13 Stewart et al took a different approach to design a CAS for lungs, using rank-ordered logistic regression models that aimed to preserve the allocation ordering of candidates within match runs. 14 Bertsimas et al 7 have modeled continuous distribution similarly to our MELD-Distance score, using MELD/OPOM with a penalty for donorrecipient distance and maintaining the allocation circle of 600 NM radius as a geographic boundary for prioritizing status 1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our CAS for liver allocation was designed using simulation with optimization to be minimally disruptive to all other priorities in the existing system while eliminating geographic boundaries. Previously, optimization methods were used to redesign district boundaries 10‐12 for liver distribution and design geographically heterogeneous circular distribution 13 . Stewart et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is paramount that changes to allocation policy should enhance transparency and allow for re-evaluation of models and rules used. In this regard, a positive aspect of this new system is the flexibility for future adjustments [40,56]. A recent study has already suggested a refinement, by using heterogeneous instead of fixed circles to further reduce geographic disparity [56].…”
Section: The Liver Transplant Debate: How Geographical Disparities Im...mentioning
confidence: 99%